Genomic variation in Saccharomyces cerevisiae influences paraquat response through differential oxidative stress and vacuolar adaptations - Cubillos-Riffo, F (Academic Press, 2025)
The conserved genetics between Saccharomyces cerevisiae and mammals makes yeast an ideal model for studying the biological effects of paraquat (PQ), an herbicide linked to Parkinson’s disease (PD) risk in humans. To determine how genetic background influences PQ toxicity, we treated four diverse yeast strains (NA, SA, WA, and WE) and assessed their physiological (growth curves), molecular (superoxide and peroxide levels), and cellular (vacuolar morphology/disaggregation) responses. PQ significantly reduced the specific growth rate (µMax) in WE and WA strains, while SA and NA remained unaffected. Superoxide and peroxide levels increased across all strains to varying degrees, with SA and WE exhibiting the highest accumulation. Furthermore, we found an inverse association between superoxide levels and µMax. PQ also induced strain-dependent vacuolar morphology shifts, from a single large organelle to fragmented vacuoles, with the susceptible WE strain displaying the most extreme disaggregation. Given the known link between lysosomal dysfunction and pesticide-induced PD, we investigated correlations between predicted missense variants in vacuolar genes and PQ responses. This analysis identified associations between fen2 variants, the human SLC17A5 ortholog, and vacuolar disaggregation. Validation using a fen2-deleted strain (Δfen2) confirmed its mechanistic role, showing increased vacuolar fragmentation, elevated oxidative markers, and compromised growth upon PQ exposure. In conclusion, our findings demonstrate that PQ susceptibility is intrinsically linked to intracellular superoxide levels and that fen2 plays a critical role in the vacuolar adaptive response to oxidative stress. The mechanisms employed by the most resistant strains may inform the development of novel therapeutics for PQ-exposed individuals. © 2025 The Author(s).